Stop procrastinating : get to work - Sherman, James R. (Crisp Pub. Menlo ParkUS, 1989)
Defines procrastination and identifies some of its consequences. Examines 15 major causes of procrastination including: lack of responsibility; lack of priorities; fatigue; and dependence on others. Provides eighteen suggestions to stop procrastinating including: reward yourself; organize and plan better; and, become more decisive. Proposes a plan of action.